KEMAMPUAN INOVASI PELAYANAN PEGAWAI - Ariefebriana, Wiyata; Basuki, Johanes; Heriyanto, Meyzi (Jurnal Ilmu Administrasi Negara, 2019)
Ability of Employee Service Innovation. This study aims to analyze the performance and tasks at the Bureau of Organization Office of the Regional Secretariat of Riau Province. The method used is descriptive qualitative. primary data obtained from interview dani. Secondary data is obtained from collecting data with documents. Data analysis used genetic data, data reduction, data presentation, and deduction of conclusions. The results of research that shows optimal performance This is evident from the factors of leadership, mastery of technology in the mastery of information technology and imperfect government programs move in its use.